Transformation оf the Ukrainian Party System after the Revolution of Dignity in 2013 - Krasnova, M. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article analyses the impact of the events of 2010-2015 on the party system of Ukraine. The recent years have been showing establishment, collapse and formation of a new party authority. It researches the main aspects causing the collapse of a «party authority», early parliamentary elections and the rule of new party elite in Verkhovna Rada. It also examines distinctive features of the transitional party systems in the post-Soviet countries on the example of Ukraine.